Role of Autologous Fibrine Glue to Decrease Seroma Volume On 14th Post Operative Day in Carcinoma Mamae Patients that Underwent Simple Mastectomy - Ahmad Iffa Maududy; Kiki Ahmad Rizki; Raden Yohana; Nadjwa Jamalek (Ikatan Ahli Bedah Indonesia, 2020)
Background: Seroma is the most significant complication that occurred after mastectomy, happen in 25% until 60% cases. Seroma are not life threatening complications, but can lead to serious morbidity, prolonged hospital stay and delay adjuvant therapy. Autologous Fibrin Glue is a hemostatic agent that can accelerate fibrin thread formation, stop vascular oozing and decrease dead space. This research was performed to evaluate Autologous Fibrin Glue function in lowering seroma volume at 14th days after simple mastectomy. Methods: This research is a clinical trial to compare average seroma volume between advance stage locally breast carcinoma patients group which are given Autologous Fibrin Glue on the surface of surgical wound, 14 days after simple mastectomy (trial group) and control group (without special treatment) with ultrasonography. Result: From 42 patients who met the inclusion criteria, divided into 2 groups, 21 patients were given Autologous Fibrin Glue on the surgical wound surface in a simple mastectomy procedure, 21 patients as a control group. The number of seromas in the treatment group was measured using ultrasound on the 14th day, fewer meaningfully than the control group, the median seroma volume in the treatment group was 9,30 mL and median seroma volume in the control group was 20.90 mL. The P value in the variable number of seroma is smaller than 0.05 (P. < 0.05) which means significant, the number of seromas measured using ultrasonography (USG) on the 14th day, fewer meaningfully in the treatment group. Conclusion: Subjects that was given Autologous Fibrin Glue on the surface of surgical wound after simple mastectomy has a lower volume of seroma compared to control group.